Queer at Camp: The Impact of Summer Camps on LGBTQ Campers in the United States - Penny Harvey; Juhwan Seo; Emily Logan (Gender a Výzkum, 2022)
The purpose of this study is to explore the ways in which LGBTQ campers and counsellors are shaped by and shape summer camp. Summer camps are often the place where many US youth begin to learn about sex and sexuality. It is a unique and important spatial locale that is understudied in both sexualities and wider sociological enquiry. To better understand the impact of summer camp experiences on sexualities, the study analyses retrospective interviews with former campers about their experiences at a summer camp, as well as podcasts and blogs. We address two key areas of camp life: sexual firsts and being openly queer at camp. Many campers are less likely to be out at camp than they are at home. The exception to this is when there are visible staff or counsellors that are out at camp. Despite not being out, many LGBTQ campers have their first sexual experience at camp, though many do not see it as sexual at the time of the act. Our findings reaffirm the importance of contact with queer people, both for LGBTQ acceptance from straight/cis people and for the self-acceptance of young queer persons. We conclude by discussing how this space is unique and how it can be improved for LGBTQ people's experiences and development at summer camps.